Study of platelet-mediated clumping adhesion phenotypes in Plasmodium falciparum malaria - Onyambu, F; Frank Onyambu (2015)
Platelet-mediated clumping of Plasmodium falciparum-infected erythrocytes (IEs) is a common property of field isolates associated with severe disease (Pain, Ferguson et al. 2001). Platelet receptors CD36 (Pain, Ferguson et al. 2001), P-Selectin (Wassmer, Taylor et al. 2008) and gC1qR (Biswas, Hafiz et al. 2007) mediate clumping. To characterize the molecular specificities of the clumping phenotype, I cloned clumping parasite line IT/C10 by limiting dilution. I characterized var gene expression in the IT/C10 clones using generic primers for the DBL tag region (Bull, Berriman et al. 2005). Clumping assays were conducted in the presence of specific reagents to delineate host factors hypothesized to contribute to development of the clumping phenotype. Finally, I conducted a clinical study with isolates from children with malaria in Kilifi, Kenya. This study shows that in parasite line IT/C10, platelet-mediated clumping is associated with Itvar30 suggesting a prominent role for the PfEMP-1 encoded by this var gene in development of platelet-mediated clumping. For IT/C10 parasites, platelet activation appears to be involved in platelet-mediated clumping. Platelet P-Selectin appears to mediate clumping using lectin-dependent interactions. To further elucidate the mechanisms that mediate clumping by host platelets, I have used a panel of platelet antagonists to delineate specific platelet activation pathways. Our results show that platelet activation plays an important role in platelet-mediated clumping. Finally, in this study, platelet-mediated clumping was associated with parasitaemia, but not with disease severity.